2022
DOI: 10.1002/aic.17881
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative principle of shape‐selective catalysis for a rational screening of zeolites for methanol‐to‐hydrocarbons

Abstract: The production of hydrocarbons for the synthesis of readily available energy and multifunctional materials is of great importance in modern society. Zeolites have proven to be a boon for the targeted regulation of specific hydrocarbon as shape‐selective catalyst in converting carbon resources. Yet our mechanistic understanding and quantitative description of shape‐selectivity of zeolite catalysis remains rather limited, which restricts the upgrade of zeolite catalysts. Herein, we proposed quantitative principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
(191 reference statements)
0
4
0
Order By: Relevance
“…Zeolite catalysts with various cavity structures mediate the reaction performance by changing the formation of crucial intermediates, olefin precursors and their involvement route in the complex reaction network based on the strong host–guest interaction of the supramolecular system, which jointly affect the MTO reaction's product selectivity. The cavity environment directly controls product distribution of the MTO reaction over cavity-type and small-pore zeolite and zeotype materials [ 34 , 38–40 ]. Liu and coworkers [ 38 ] established the definitive correlation between the catalyst's cavity structure and product selectivity by assessment of all the elementary steps of the complete catalytic cycles at the molecular level, and found that predominant formation of olefin products depended on the generation of HCP species, the formation of the olefin precursor and the reaction route together were mediated by different cavity-type zeolite or zeotype catalysts.…”
Section: Cavity-controlled Mto Reaction Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…Zeolite catalysts with various cavity structures mediate the reaction performance by changing the formation of crucial intermediates, olefin precursors and their involvement route in the complex reaction network based on the strong host–guest interaction of the supramolecular system, which jointly affect the MTO reaction's product selectivity. The cavity environment directly controls product distribution of the MTO reaction over cavity-type and small-pore zeolite and zeotype materials [ 34 , 38–40 ]. Liu and coworkers [ 38 ] established the definitive correlation between the catalyst's cavity structure and product selectivity by assessment of all the elementary steps of the complete catalytic cycles at the molecular level, and found that predominant formation of olefin products depended on the generation of HCP species, the formation of the olefin precursor and the reaction route together were mediated by different cavity-type zeolite or zeotype catalysts.…”
Section: Cavity-controlled Mto Reaction Behaviormentioning
confidence: 99%
“…Furthermore, recently, Liu and coworkers [ 34 ] presented a quantitative shape selectivity for zeolite catalysis, which involves thermodynamics, reaction kinetics and molecular diffusion in a confined zeolite framework. The product’s distribution derives from the competitive effect of molecular diffusion and secondary reactions between hydrocarbon compounds, the ratio of selectivity of C y = /C 2 = and alkane/alkene.…”
Section: Cavity Modification For Super Shape Selectivitymentioning
confidence: 99%
See 2 more Smart Citations